Monitoring the Success of Hydroseeding Application Using Microbial Diversity in Some Post-Coal Mining Revegetation Areas, South Kalimantan: Monitoring the Success of Hydroseeding Application Using Microbial Diversity - Fadhil Anshari, Muhammad; Achmad Rinaldo Fernandes , Adji; Setyo Leksono, Amin; Arisoesilaningsih, Endang (Journal of Tropical Life Science, 2024)
Successful revegetation improves the whole ecosystem's integrity, including microbe habitat. The goal of this study is to monitor the success of hydroseeding applications in some post-coal mining revegetation areas using microbial diversity. This study was conducted by sampling soils at a reference site (HS) and three revegetation areas (Kuni, AR07, AH). Kuni represents a 12-year-old monoculture replantation area while AR07 and AH are representations of hydroseeded areas with different ages, 5.5 years and 3 months old. Soil samples were then analyzed to determine N, P, K, and CEC, and extracted using the CTAB/SDS method, resulting in the total genome DNA. The genes of 16S rRNA were amplified using a specific primer, followed by product quantification and purification. Sequencing libraries were generated using the NEBNext® UltraTM DNA Library Pre Kit for Illumina. The library was sequenced on Illumina platform, and 250 bp paired-end reads were generated. The data were then analyzed using Anova, biplot, and cluster analysis. Results showed that AR07 was the most similar site to HS based on soil chemical properties and had the highest value of all alpha diversity indices. The dominant presence of Burkholderiales in AH indicated improvement in soil chemical properties. The soil microbial diversity PCA analysis revealed that the similarity between HS and AH was high. It was indicating a better success of hydroseeding at AH with shorter revegetation time as compared to the monoculture replantation site in Kuni. Hydroseeding using local pioneer species is highly recommended for postcoal mining revegetation.